PRELIMINARY RESEARCH ON THE SURVIVAL STRATEGIES AMONG PALA’O PEOPLE IN BANGGI ISLAND - Dzurizah Ibrahim; Jalihah Md. Shah (Jurnal Community, 2020)
This paper is based on a preliminary study of the survival of Pala’o ethnic group living in Banggi Island located in the northern part of Sabah, Malaysia. Banggi Island is inhabited by various ethnic groups and dominated by Bajau Ubian, Dusun Bonggi, Suluk, Kegayan, Bajau Sama’ and Molbog ethnic groups. Today, Banggi Island is also inhabited by the ethnic of Pala’o, also known as Bajau Laut or sea gypsies, and Palauh/Sama Dilaut, which originate in the Semporna waters of the Sulu and Celebes Sea. Based on the qualitative approach through in-depth interviews, the Sea Gypsies off the coast of Karakit town, Banggi Island was found to be able to adapt to changes in the environment and adapt it to their suitability. The need to continue living is seen as an essential part of this ethnic 'migration'. The study found that for survival, the Pala'o tribe in the context of this study adopted four survival strategies namely sea migration to land, physical strategy, social strategy and economic strategy. However, the fate of Pala'o's ethnic group remained largely unchanged. They are still subject to poverty and they have always been, and still remain, ethnic 'without citizenship'. The success of a survival strategy is seen to be closely related to the economic sector and the work it does, knowledge, skills and education but it does not apply to this Pala'o tribe. Their lives are still being faced by the hardships of the poor but their insistence on life has given them a chance to continue living even though their lives on the land are different from their life's experiences in the great sea.